Tinjauan Hukum terhadap Jasa Tukang Gigi Yang Melebihi Wewenangnya: Analisis Peraturan Menteri Kesehatan Nomor 39 tahun 2014 - Ciptaningsih, Wahyu; Radian, Muhammad Luthfi (Universitas Islam Negeri Alauddin Makassar, 2024)
Dental artisan is a dentist's specialty. The large number of dental artisan who do not follow the health benchmarks set out in Minister of Health Regulation Number 39 of 2014 makes it seem as if the norms created are meaningless. In fact, there are quite a few cases where dental artisan carry out fixed braces treatment on their patients. This research will discuss the legal regulation of dental artisan that exceed their authority in terms of Minister of Health Regulation No. 39 of 2014. The aim of this research is to find out the legal regulations regarding permits to practice dental artisan in Indonesia based on Minister of Health Regulation Number 39 of 2014 and to find out legal sanctions for providers of dental artisan who exceed their authority. In completing this research, the method used was the normative juridical method. The study results show that dentists based on Minister of Health Regulation no. 39/2014 is only allowed to make and install partial and/or full removable dentures using heat curing acrylic material. The sanctions that can be imposed on dentists who exceed their authority can be subject to administrative sanctions in the form of a written warning, temporary or permanent license revocation.